2017
DOI: 10.1089/ten.tea.2016.0461
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin Scaffolds Containing Partially Sulfated Cellulose Promote Mesenchymal Stem Cell Chondrogenesis

Abstract: Articular cartilage has a limited capacity to heal after damage from injury or degenerative disease. Tissue engineering constructs that more closely mimic the native cartilage microenvironment can be utilized to promote repair. Glycosaminoglycans (GAGs), a major component of the cartilage extracellular matrix, have the ability to sequester growth factors due to their level and spatial distribution of sulfate groups. This study evaluated the use of a GAG mimetic, cellulose sulfate, as a scaffolding material for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Other studies that have used the same media with chondrocytes reported a limited in vitro secretion of Collagen Type II (Sun, Wang, & Kaplan, ); higher Collagen Type I than Collagen Type II expression (Schwager, Hoeller, Wolfram, & Richard, ); and lower secretion of Procollagen Type II C propeptide in chondrocytes than the one of undifferentiated human bone marrow stem cells (Giavaresi et al, ). We consider unlikely that the crowder used could have induced dedifferentiation, as CR has been shown to enhance chondrogenesis in human bone marrow stem cell cultures (Cigognini et al, ) and sulphated polysaccharides, like CR, have been shown repeatedly to enhance chondrogenesis (Derfoul et al, ; Lohmander et al, ; Merceron et al, ; Park et al, ; Portocarrero‐Huang et al, ; Toegel et al, ; Varghese et al, ; Zhao et al, ). Considering that (a) the ratio between Collagen Type II and Collagen Type I is the main indicator of chondrogenic phenotype and its changes are associated with dedifferentiation (Hubka, Dahlin, Meretoja, Kasper, & Mikos, ; Marlovits, Hombauer, Truppe, Vecsei, & Schlegel, ; O'Driscoll, Commisso, & Fitzsimmons, ); (b) collagen expression, synthesis, secretion, and deposition are not always correlated (Cote et al, ; Grimmer et al, ; Shahdadfar et al, ); and (c) the almost undetectable deposited collagen in the absence of MMC, MMC may be adopted for characterising the type of ECM produced and for assessing the effectiveness of future developed redifferentiation media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that have used the same media with chondrocytes reported a limited in vitro secretion of Collagen Type II (Sun, Wang, & Kaplan, ); higher Collagen Type I than Collagen Type II expression (Schwager, Hoeller, Wolfram, & Richard, ); and lower secretion of Procollagen Type II C propeptide in chondrocytes than the one of undifferentiated human bone marrow stem cells (Giavaresi et al, ). We consider unlikely that the crowder used could have induced dedifferentiation, as CR has been shown to enhance chondrogenesis in human bone marrow stem cell cultures (Cigognini et al, ) and sulphated polysaccharides, like CR, have been shown repeatedly to enhance chondrogenesis (Derfoul et al, ; Lohmander et al, ; Merceron et al, ; Park et al, ; Portocarrero‐Huang et al, ; Toegel et al, ; Varghese et al, ; Zhao et al, ). Considering that (a) the ratio between Collagen Type II and Collagen Type I is the main indicator of chondrogenic phenotype and its changes are associated with dedifferentiation (Hubka, Dahlin, Meretoja, Kasper, & Mikos, ; Marlovits, Hombauer, Truppe, Vecsei, & Schlegel, ; O'Driscoll, Commisso, & Fitzsimmons, ); (b) collagen expression, synthesis, secretion, and deposition are not always correlated (Cote et al, ; Grimmer et al, ; Shahdadfar et al, ); and (c) the almost undetectable deposited collagen in the absence of MMC, MMC may be adopted for characterising the type of ECM produced and for assessing the effectiveness of future developed redifferentiation media.…”
Section: Discussionmentioning
confidence: 99%
“…Although MMC (neutral and nonsulphated crowder cocktail, Ficoll 70 and Ficoll 400, was used) did not significantly increase chondrogenesis in chondrocyte (Chen et al, ) and adipose‐derived stem cell (Patrikoski et al, ) cultures, it significantly increased chondrogenesis in human bone marrow stem cell cultures (negatively charged and highly sulphated crowder, carrageenan [CR], was used; Cigognini et al, ). Considering that sulphated polysaccharides have been shown repeatedly to enhance chondrogenesis (Derfoul, Miyoshi, Freeman, & Tuan, ; Lohmander, Hascall, & Caplan, ; Merceron et al, ; Park et al, ; Portocarrero‐Huang et al, ; Toegel et al, ; Varghese et al, ; Zhao, Wang, Chen, & Chen, ), herein, we hypothesised that the combination of a commercially available chondrogenic media with MMC will enable chondrogenic phenotype maintenance during in vitro chondrocyte expansion and increase cartilage‐specific ECM deposition, enabling that way the development of a tissue‐engineered cartilage substitute. To validate our hypothesis, human chondrocytes at Passage 2 were cultured in monolayer and alginate beads with and without MMC.…”
Section: Introductionmentioning
confidence: 99%
“…A general concept is the introduction of sulfate groups into the backbones of natural polysaccharides that lack intrinsic sulfate groups to endow them with analogous biological activities to that of GAG . For example, cellulose sulfate (CS), chitosan sulfate (CHS), pullulan sulfate, heparosan sulfate, and sulfated locust bean gum (LBG) as half‐esters of these polysaccharides showed anticoagulant and antiviral functions, supported cell growth and differentiation, and were used therefore as drug‐release systems and implants in living organisms (Scheme ) . Hence, these biomimetic substances with superior or comparable heparinoid activity to that of GAGs and predictable structures in a purified state are attractive for biomedical and bioengineering applications .…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] For example, cellulose sulfate( CS), chitosan sulfate (CHS), pullulan sulfate, heparosan sulfate,a nd sulfated locust bean gum (LBG) as half-esters of these polysaccharides showed anticoagulant and antiviral functions, supported cell growth andd ifferentiation, and were used therefore as drug-release systemsa nd implants in living organisms (Scheme 2). [21][22][23][24][25] Hence, these biomimetic substances with superior or comparable heparinoid activity to that of GAGs and predictable structuresi napurified state are attractive for biomedicala nd bioengineering applications. [21][22][23][24][25] This Minireview providesasummary of recent research into sulfated polysaccharides,w hich include CS, CHS, and af ew other polysaccharides sulfates, in the last decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation